2015
DOI: 10.1128/aac.04124-14
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of AZD0914, a New Spiropyrimidinetrione DNA Gyrase/Topoisomerase Inhibitor with Potent Activity against Gram-Positive, Fastidious Gram-Negative, and Atypical Bacteria

Abstract: AZD0914 is a new spiropyrimidinetrione bacterial DNA gyrase/topoisomerase inhibitor with potent in vitro antibacterial activity against key Gram-positive (Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pneumoniae, Streptococcus pyogenes, and Streptococcus agalactiae), fastidious Gram-negative (Haemophilus influenzae and Neisseria gonorrhoeae), atypical (Legionella pneumophila), and anaerobic (Clostridium difficile) bacterial species, including isolates with known resistance to fluoroquinolone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 17 publications
4
69
0
Order By: Relevance
“…The Ser 467 Asn substitution has been observed in the GyrB sequence of a clinical isolate, although the AZD0914 MIC against this isolate was 0.125 g/ml (16). Furthermore, the presence of Asn in this position is found in the GyrB and ParE proteins of key Gram-positive pathogens, such as S. aureus and S. pneumoniae, against which AZD0914 is active (27). Interestingly, the equivalent position is a Ser in both GyrB and ParE of key Gram-negative pathogens, and N. gonorrhoeae is the only organism that has a different residue in each subunit, with a Ser in this position in GyrB and an Asn in ParE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The Ser 467 Asn substitution has been observed in the GyrB sequence of a clinical isolate, although the AZD0914 MIC against this isolate was 0.125 g/ml (16). Furthermore, the presence of Asn in this position is found in the GyrB and ParE proteins of key Gram-positive pathogens, such as S. aureus and S. pneumoniae, against which AZD0914 is active (27). Interestingly, the equivalent position is a Ser in both GyrB and ParE of key Gram-negative pathogens, and N. gonorrhoeae is the only organism that has a different residue in each subunit, with a Ser in this position in GyrB and an Asn in ParE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-resistance between AZD0914 and other important Gram-positive class agents, including fluoroquinolones, ␤-lactams, macrolides, and glycopeptides, was not observed. The current indication being pursued for AZD0914 is uncomplicated gonococcal infections with additional in vitro activity demonstrated against other organisms responsible for sexually transmitted infections (STI), including C. trachomatis (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…AZD0914 has a primary spectrum of activity that includes clinically relevant Gram-positive and fastidious Gram-negative bacterial species, including N. gonorrhoeae (12)(13)(14)(15). Published in vitro data on Chlamydia trachomatis and Chlamydia pneumoniae have shown that AZD0914 also has activity against these species (16).…”
mentioning
confidence: 99%
“…ETX0914 has displayed potent in vitro antibacterial activity against N. gonorrhoeae, including multidrugresistant strains, certain Gram-positive organisms, such as Staphylococcus aureus and Streptococcus pneumoniae, and fastidious Gramnegative organisms, such as Haemophilus spp. and Moraxella catarrhalis, and also atypical and anaerobic organisms (12)(13)(14)(15). Cross-resistance between ETX0914 and fluoroquinolones has not been observed (16).…”
mentioning
confidence: 99%